Rapid Repeat Birth: Meaning-Making Among Multiparous Adolescent Mothers. - Reddy, Julia. (2017)
Abstract: This study examined initial interpretations of, and transitions to, motherhood among adolescents who have experienced rapid repeat births. The primary sample was 19 adolescent mothers, enrolled in a universal home visiting program, who gave birth to a second child within 24 months of their initial birth. Findings suggest a strong presence of positive interpretations of motherhood and its effects on the life trajectories of the adolescents. Although significant heterogeneity existed, four modal narratives emerged, nesting the subjective understandings of motherhood within contexts of stability and social support. Additionally, in a comparison between rapid repeat birth mothers and non-rapid repeat birth mothers in a larger adolescent sample, significant differences in rates of maltreatment history, intimate partner relationship status, and receipt of home visitation emerged. Adolescent mothers who had experienced rapid repeat birth had significantly higher rates of maltreatment histories that mothers who did not have rapid repeat births. Rapid repeat birth mothers received significantly fewer home visits, and rapid repeat birth mothers were more likely to be involved with the father of their children.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Child Development.; Advisor: Fran Jacobs.; Committee: Janythi Mistry, Rebecca Strimer, and Fran Jacobs.; Keywords: Developmental psychology, Public policy, and Social work.